ADTU-08 Incidence and management of immunotherapy-induced colitis in a tertiary IBD centre – clinical practice data. (8th June 2018) - Gupta, T; Cheung, V; Boddy, L; Harrogate, E; Liew, I; Rudra, R; Payne, M; Middleton, M; Brain, O
Abstract : Introduction: Checkpoint inhibitors are a novel anti-cancer therapy that are standard of care in metastatic melanoma, non-small cell lung and renal cancer. 1 CTLA-4 inhibitors (e.g Ipilimumab) and PD-1 inhibitors (Nivolumab, Pembrolizumab) can be used separately or in combination for melanoma, whereas singlet therapy is currently the norm for others. Their immune inhibition is non-specific, leading to a number of immune-related adverse events (irAEs) including colitis, hepatitis and pancreatitis. 2 Combination therapy is known to cause more irAEs than single-agent PD-1 inhibition. There are limited real-world clinical data describing the incidence and management of these GI irAEs. Aims: 1) To determine the incidence of GI irAEs in a tertiary oncology centre. 2) To analyse the management and outcome of GI irAEs within a tertiary oncology and IBD centre. Methods: Retrospective single–centre review. Melanoma, renal and lung cancer patients receiving Ipilimumab ± Nivolumab ± Pembrolizumab between Dec 2011 and June 2017 were identified from the oncology prescribing database. The electronic patient record was used to determine the incidence of GI side effects. Investigations, treatment, and outcome data were collated. Results: 272 patients who received immunotherapy were identified. There was a higher incidence of diarrhoea and hepatitis in those receiving simultaneous or sequential dual therapy versus monotherapy (Figure 1). The incidence of diarrhoea for dual therapy (n=18/29, 62%) was in excess of that described in trial data (44%). 3 Colitis requiring infliximab or colectomy was exclusively associated with ipilimumab therapy, with dual immunotherapy more likely to require infliximab (13%) versus monotherapy (4%). Colitis was generally associated with a raised CRP and low albumin. There was significant variability in symptoms, time of onset, and in management decisions. Conclusions: Dual therapy with CTLA-4 and PD-1 inhibitors may result in a higher incidence of colitis than described in clinical trials. Although guidelines exist, 2 there is no clear biological threshold for timing of therapy initiation and escalation, resulting in variability in care. This case series demonstrates that irAE colitis is a common problem that has implications for healthcare provision and care standardisation. Complete management and outcome data will be presented. Reference: . Gupta A, et al. Aliment. Pharmacol. Ther (2015);42:406–417. . Cheng R, et al. J . GastroenterolHepatol (2015);30:657–666. . Larkin J, et al. NEJM 2015;373:23–34.